Chelation‐Assisted Palladium‐Catalyzed γ‐Arylation of Aliphatic Carboxylic Acid Derivatives. Issue 8 (23rd February 2017) - Dey, Aniruddha; Pimparkar, Sandeep; Deb, Arghya; Guin, Srimanta; Maiti, Debabrata
Abstract: A palladium(II)‐catalyzed protocol for the highly regioselective remoteγ ‐C–H arylation of aliphatic carboxylic acid has been disclosed. The 8‐aminoquinoline moiety as an intramolecular bidentate chelator was found to be suitable for thisγ ‐C–H arylation. Various aryl iodides successfully produced the regioselectively mono‐arylated products with negligible diarylation. Functional group tolerance and easy‐to‐handle reaction conditions make this method attractive. Abstract :